Analisis Sensitivitas dalam Optimalisasi Produksi UD Mekar Sari Karang Klesem Menggunakan Program Linier dengan Metode Simpleks Diperbaiki - Winarni, Ambar; Kartika, Dwiani Listya (JOSTECH Journal of Science and Technology, 2024)
The research aimed to optimize the production of crackers in order to achieve maximum profit at the UD Mekar Sari Karangklesem factory by applying the simplex method. This research used a descriptive quantitative research approach and literature study methods to support the preparation of this research. The data used is secondary data which includes the amount of each raw material needed, the purchase price of each raw material, the selling price of each type of cracker and the yield of each type of cracker produced. UD Mekar Sari is a cracker factory that produces gendar crackers, soto crackers, onion crackers and makaroni crackers. The results of this study indicate that after going through the steps of the simplex method which was improved it was found that an optimum profit of IDR 11,530,000 would be achieved by producing 200 kg of gendar crackers, 80 kg of soto crackers, 100 kg of onion crackers and 80 kg of makaroni crackers . Based on the data on the composition and supply of raw materials for the production of the four types of crackers, data analysis and processing can be carried out by formulating them into a linear program using the improved simplex method. This method is considered more efficient than the improved simplex method. The results of the sensitivity analysis that only limited changes in coefficient value at objective function (the profit each crackers) and the constants right side constraints (the capacity of supply of the raw materials) show that profit remain in optimal condition if the change of coefficient value at objective function and the constants right side constraints between the range being resulted.